Antioxidant activity of silver nanoparticles tiwai onion callus extract (Eleutherine palmifolia L.Merr) - Amrullah Muhammad Hapizi; Yanti Puspita Sari; Linda Oktavianingsih; Widya Fajariani (Jurnal Biolokus : Jurnal Penelitian Pendidikan Biologi dan Biologi, 2026)
Silver nanoparticles (AgNPs) are a type of nanotechnology with low chemical reactivity and high stability. AgNPs biosynthesis using plant extracts has advantages compared to other methods because it is simpler and more environmentally friendly. Tiwai onion is a medicinal plant native to Borneo that contains bioactive compounds flavonoid, alkaloid, flavanoid, dan saponin and can be used as a material for producing AgNPs. Onion tiwai calli from tissue culture is an alternative source of material that can be used to avoid excessive use of natural materials. This study aimed to determine the optimum concentration of silver nitrate for the stability of AgNPs and the optimum antioxidant activity of Tiwai onion callus extract and AgNPs. The research design used was a completely randomized design with five treatments, namely, AgNO3 concentrations of 0, 0.5; 1; 1., and 2 mM. This research consisted of tiwai onion callus induction, callus extraction using the maceration method, AgNPs synthesis of onion callus tiwai, and antioxidant activity test using the DPPH method. Temperature, pH, and absorbance data were examined in Microsoft Excel, while antioxidant activity was determined via regression based on IC50 values. The results showed that an AgNO3 concentration of 1 mM was the most stable for forming AgNPs. The highest antioxidant activity was found in the AgNPs of Tiwai onion callus extract, with an IC50 value of 48.148 ppm. In conclusion, the antioxidant activity of AgNPs in Tiwai onion callus extract was higher than that of the callus extract.